Assessing the Influence of Green Supply Chain Initiatives on Corporate Performance Using SmartPLS - Anwar, Nizirwan; Wahyudin Anugrah, Rio; Jensen, Henrik (APTISI Transactions on Management (ATM), 2025)
This study investigates the influence of Green Supply Chain Initiatives (GSCI) on Corporate Performance (CP), emphasizing the mediating role of Operational Efficiency (OE). Using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS, the research analyzes survey data collected from SESINDO organizations. GSCI, encompassing practices such as green procurement, eco-design, and waste management, are examined for their impact on financial, operational, and environmental performance. The findings reveal a significant positive relationship between GSCI and CP, highlighting that sustainable practices enhance financial outcomes, operational efficiencies, and environmental impact reduction. Furthermore, OE is identified as a partial mediator, amplifying the benefits of GSCI on CP. This underscores the importance of optimizing resource utilization and streamlining processes to maximize the impact of sustainability initiatives. The study contributes to theory by integrating the Resource-Based View (RBV) and Institutional Theory, offering a comprehensive understanding of GSCI adoption and outcomes. Practically, it provides actionable insights for business leaders and policymakers to promote sustainability while achieving competitive advantage. Despite its contributions, the study acknowledges limitations, such as its cross-sectional design and regional focus, and suggests future research in diverse contexts. This research underscores the transformative potential of GSCI in driving sustainable corporate success.